Transaksi Derivatif Lindung Nilai (Hedging) Pada PT. Krakatau Steel (Persero) Tbk - Rani Zahra; Aulia Diana Savitri; Elice Violeta; Siti Rodiah (Jurnal Mutiara Ilmu Akuntansi, 2023)
The purpose of this research is to learn more about PT Krakatau Steel (Persero) Tbk's (the company under investigation) use of derivative hedging transactions. In this study, content analysis was applied as a qualitative methodology. The 2020 financial statements are the data source for this study. According to the data, PT Krakatau Steel (Persero) Tbk makes use of derivative instruments as a form of risk management. Swaps, spot trades, forward contracts, and options are all examples of derivative transactions. The corporation also employs derivative instruments to reduce exposure to uncertainty. Due to the size of its operations, PT Krakatau Steel (Persero) Tbk is a prime candidate for the usage of derivative instruments. Companies of PT Krakatau Steel (Persero) Tbk's size typically have the financial resources to incur all the costs necessary to use derivatives in order to reap the economic benefits they provide. The hedging effect is expected by the company to be able to mitigate exchange rate risks and price fluctuations. Therefore, hedging can make it easier for companies to make funding plans and buying and selling transactions carried out by companies.